Chromosome-level genome assembly of Gynostemma pentaphyllum provides insights into gypenoside biosynthesis. (9th September 2021) - Huang, Ding; Ming, Ruhong; Xu, Shiqiang; Wang, Jihua; Yao, Shaochang; Li, Liangbo; Huang, Rongshao; Tan, Yong
Abstract: Gynostemma pentaphyllum (Thunb.) Makino is an economically valuable medicinal plant belonging to the Cucurbitaceae family that produces the bioactive compound gypenoside. Despite several transcriptomes having been generated for G. pentaphyllum, a reference genome is still unavailable, which has limited the understanding of the gypenoside biosynthesis and regulatory mechanism. Here, we report a high-quality G. pentaphyllum genome with a total length of 582 Mb comprising 1, 232 contigs and a scaffold N50 of 50.78 Mb. The G. pentaphyllum genome comprised 59.14% repetitive sequences and 25, 285 protein-coding genes. Comparative genome analysis revealed that G. pentaphyllum was related to Siraitia grosvenorii, with an estimated divergence time dating to the Paleogene (∼48 million years ago). By combining transcriptome data from seven tissues, we reconstructed the gypenoside biosynthetic pathway and potential regulatory network using tissue-specific gene co-expression network analysis. Four UDP-glucuronosyltransferases (UGTs), belonging to the UGT85 subfamily and forming a gene cluster, were involved in catalyzing glycosylation in leaf-specific gypenoside biosynthesis. Furthermore, candidate biosynthetic genes and transcription factors involved in the gypenoside regulatory network were identified. The genetic information obtained in this study provides insights into gypenoside biosynthesis and lays the foundation for further exploration of the gypenoside regulatory mechanism.